CDK1-dependent phosphorylation of EZH2 suppresses methylation of H3K27 and promotes osteogenic differentiation of human mesenchymal stem cells - Wei, Yongkun; Chen, Ya-Huey; Li, Long-Yuan; Lang, Jingyu; Yeh, Su-Peng; Shi, Bin; Yang, Cheng-Chieh; Yang, Jer-Yen; Lin, Chun-Yi; Lai, Chien-Chen; Hung, Mien-Chie (Nature cell biology, 2011)
The Polycomb group protein EZH2 promotes trimethylation of histone H3K27 and gene silencing. Cdk1 is found to phosphorylate EZH2 to inhibit its methyltransferase activity, affecting EZH2-target genes involved in osteogenic differentiation. Enhancer of zeste homologue 2 (EZH2) is the catalytic subunit of Polycomb repressive complex 2 (PRC2) and catalyses the trimethylation of histone H3 on Lys 27 (H3K27), which represses gene transcription. EZH2 enhances cancer-cell invasiveness and regulates stem cell differentiation. Here, we demonstrate that EZH2 can be phosphorylated at Thr 487 through activation of cyclin-dependent kinase 1 (CDK1). The phosphorylation of EZH2 at Thr 487 disrupted EZH2 binding with the other PRC2 components SUZ12 and EED, and thereby inhibited EZH2 methyltransferase activity, resulting in inhibition of cancer-cell invasion. In human mesenchymal stem cells, activation of CDK1 promoted mesenchymal stem cell differentiation into osteoblasts through phosphorylation of EZH2 at Thr 487. These findings define a signalling link between CDK1 and EZH2 that may have an important role in diverse biological processes, including cancer-cell invasion and osteogenic differentiation of mesenchymal stem cells.